The Effect of Starvation on Plastid Number and Photosynthetic Performance in the Kleptoplastidic Dinoflagellate Amylax triacantha. (23rd May 2014) - Kim, Miran; Kim, Kwang Young; Nam, Seung Won; Shin, Woongghi; Yih, Wonho; Park, Myung Gil
Abstract The dinoflagellate Amylax triacantha is known to retain plastids of cryptophyte origin by engulfing the mixotrophic ciliate Mesodinium rubrum, itself a consumer of cryptophytes. However, there is no information on the fate of the prey's organelles and the photosynthetic performance of the newly retained plastids in A. triacantha. In this study, we conducted a starvation experiment to observe the intracellular organization of the prey's organelles and temporal changes in the photosynthetic efficiency of acquired plastids in A. triacantha. The ultrastructural observations revealed that while the chloroplast‐mitochondria complexes and nucleus of cryptophyte were retained by A. triacantha, other ciliate organelles were digested in food vacuoles. Acquired plastids were retained in A. triacantha for about 1 mo and showed photosynthetic activities for about 18 d when measured by a pulse‐amplitude modulation fluorometer.